2011
DOI: 10.1103/physreve.83.037102
|View full text |Cite
|
Sign up to set email alerts
|

Self-sustaining oscillations in complex networks of excitable elements

Abstract: Random networks of symmetrically coupled, excitable elements can self-organize into coherently oscillating states if the networks contain loops (indeed loops are abundant in random networks) and if the initial conditions are sufficiently random. In the oscillating state, signals propagate in a single direction and one or a few network loops are selected as driving loops in which the excitation circulates periodically. We analyze the mechanism, describe the oscillating states, identify the pacemaker loops and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…As long as the graph contained a cycle of 5 or more nodes without shortcuts, there seemed to be patterns possible. In a recent paper [14], McGraw and Menzinger looked at the existence of sustained activity in a random network with 200 nodes and exactly 3 connections per node. For modest strength coupling, they found that the probability of a sustained oscillation was nearly 1, but that this dramatically fell off as the coupling strength increased; in this case, initial data went to synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…As long as the graph contained a cycle of 5 or more nodes without shortcuts, there seemed to be patterns possible. In a recent paper [14], McGraw and Menzinger looked at the existence of sustained activity in a random network with 200 nodes and exactly 3 connections per node. For modest strength coupling, they found that the probability of a sustained oscillation was nearly 1, but that this dramatically fell off as the coupling strength increased; in this case, initial data went to synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…Network connections of nonoscillatory elements, for instance, give rise to such dynamics and have been studied in various contexts, including gene networks [1], epidemic spreading dynamics [2][3][4][5], and generic excitable units [6][7][8][9][10], Excitable units undergo oscillations in many ways: Simple two excitable systems can exhibit sustained dynamics when delay-coupled [11]; spatially extended excitable media can produce sustained spiral waves by introducing a perturbation leading to the formation of a spiral core [12]; one can even consider interactions at a distance through nonlocal links embedded in spatially extended systems [13][14][15][16], which eventually forms network structures composed of wave propagation and nonlocal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of work on collective activity patterns in neuronal systems [30][31][32][33][34][35]. This activity relates to proactive functions of the brain, e.g., attention and memory [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism for self-sustaining collective activity in such systems is based on the existence of cycles in networks, which effectively serve as feedback loops [15,38]. Such cycles, also called reverberators, are abundant even in random networks [31][32][33]. Recent research has focused on understanding how the loops contribute to sustained activity and how their embedding in a network affects the activity patterns [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation